Increasing Customer Value in Trade Finance Industry - Tan, Siew Lin (2013)
The purpose of this research effort is to provide an understanding of customer value, the process of customer value creation and delivery focused on Trade Finance (TF) in financial services. For customers of trade finance, it is important that the service effectively provides customer value. Service offerings are intangible and increasing value to meet customers’ expectations like price, quality and tailored services are essential to customer value strategy in trade finance. The identification of the critical attributes of customer value will be useful to serve as a guide for trade finance provider to upgrade their current service standards. From the literature, customer value dimensions such as delivery of services, branding of service provider, procedural and advisory services have emerged from quality and performance, and price for value of money(Zeithaml, 1988; Holbrook, 1994). To achieve the above purpose, an exploratory study was conducted by way of qualitative data through interviews. Data collected revealed some pattern of important factors that influence the choice of trade financing over other types of financing offered by competitors. The research confirms that trade financing is the preferred financing because of its many benefits which contribute to customer value. Among these are settlement of purchases pending proceeds of payment; get payment discounts for early settlement; cost of interest in TF is cheaper than overdraft; double savings with rebates from suppliers and lower cost of interest. The existence of such features and elements establish the superiority of one trade finance service provider above another. Limitations the researcher faced in conducting interviews for this research are that in-depth interviews are not objective but prone to biasness. The area of research is confined to Ipoh and Klang Valley. Also, one has to recognize the varied challenges offered by the type of trade finance i.e. local or international versus payment terms, nature of goods, financier’s ability to mitigate transaction risk, ability and knowledge of financier to advise customer to seek certain documentary evidence to assist their customer to emerge as a winner. Cross border transactions have their own challenges, complexities and risks.